Effect of simulated rainfall during wheat seed development and maturation on subsequent seed longevity is reversible. Issue 1 (8th January 2016) - Ellis, Richard H.; Yadav, Gajender
Abstract: Poor wheat seed quality in temperate regions is often ascribed to wet production environments. We investigated the possible effect of simulated rain during seed development and maturation on seed longevity in wheat ( Triticum aestivum L.) cv. Tybalt grown in the field (2008, 2009) or a polythene tunnel house (2010). To mimic rain, the seed crops were wetted from above with the equivalent of 30 mm (2008, 2009) or 25 mm rainfall (2010) at different stages of seed development and maturation (17–58 DAA, days after 50% anthesis), samples were harvested serially, and subsequent air-dry seed longevity estimated. No pre-harvest sprouting occurred. Seed longevity ( p 50, 50% survival period in experimental hermetic storage at 40°C with c . 15% moisture content) in field-grown controls increased during seed development and maturation, attaining maxima at 37 (2008) or 44 DAA (2009); it declined thereafter. Immediate effects of simulated rain at 17–58 DAA in field studies (2008, 2009) on subsequent seed longevity were negative but small, e.g. a 1–4 d delay in seed quality improvement for treatments early in development, but with no damage detected at final harvests. In rainfall-protected conditions (2010), simulated rain close to harvest maturity (55–56 DAA) reduced longevity immediately and substantially, with greater damage from two sequential days of wetting than one; again, later harvests provided evidence of recovery in subsequent longevity. In the absence of pre-harvest sprouting, the potentially deleterious effects of rainfall to wheat seed crops on subsequent seed longevity may be reversible in full or in part.